Principles of marketing - Kotler, Philip; Armstrong, Gary (Gary M.); Balasubramanian, Sridhar; Agnihotri, Parfulla Y. (Hoboken, NJ; India : Pearson India Education Pvt. Ltd., 2023)
"The nineteenth edition of Principles of Marketing reflects the major trends and shifting forces that impact marketing in this digital age of customer value, engagement, and relationships"--
Revised edition of Principles of marketing, 2019.
Includes bibliographical references and index.
PHR
Book Finder International
Trim Education
Keywords: Marketing; Phymarcy; Pharmaceutical industry